THERMAL-BEHAVIOR OF SURFACE-COATED MATERIALS IN CONCENTRATED SLIDING CONTACTS - AHN, HS; ROYLANCE, BJ (BUTTERWORTH-HEINEMANN LTD, 1992)
The thermal behaviour of layered solids, typified in practice by surface coated materials, is evaluated for the specific case of a fast moving heat source. This is intended to represent the particular instance of solids in sliding contact and the consequences of friction. The finite difference method has been utilized to establish the temperature distributions at the surface and also the sub-surface region for coating materials which are either less conductive or more conductive than the substrate to which they are attached. The effects of variation in layer thickness, and also the load, speed and friction coefficient, are evaluated.